Berth allocation and quay crane-yard truck assignment considering carbon emissions in port area. (17th April 2019) - Wang, Tingsong; Li, Man; Hu, Hongtao
As environmental issues become increasingly prominent, the green port has been the focus of marine industry to sustain the development of global economy. Carbon emissions of port area mainly come from water area and land area of port. The effective resource allocation and equipment assignment can not only reduce the carbon emissions, but also improve the service efficiency. Thus, this paper considers the berth-quay crane-yard truck allocation problem (B-QC-YTAP) and formulates it as a multi-objective model, where the objectives are to minimise the total carbon emissions in port area, and minimise the average waiting time in port and departure delay for each vessel. To solve the proposed model as well as obtain the Pareto optimal solutions, the non-dominated sorting genetic algorithm II (NSGA-II) is also introduced. Finally, a numerical experiment is conducted to test the effectiveness of model and algorithm, followed by the trade-off analysis between the two objectives.